PENGARUH ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA EIGER STORE PEMATANGSIANTAR - Nurwilda, Melisa; Rezeki, Sri (Media Mahardhika, 2024)
This research aims to analyze the influence of electronic word of mouth on product purchasing decisions at the Eiger Store Pematangsiantar. The study uses a quantitative research method, with primary data obtained from questionnaires distributed to respondents. The data collection technique employed simple random sampling, targeting a population of 100 consumers of Eiger Store Pematangsiantar. Data processing was conducted using the SPSS 26 application. The results indicate that both electronic word of mouth and brand image variables have a positive and significant partial effect on purchasing decisions for Eiger products. Additionally, the adjusted R-squared coefficient of determination shows that electronic word of mouth and brand image contribute to purchasing decisions.